Handbook of Leaving Religion (Brill handbooks on contemporary religion, 2020)
The Handbook of Leaving Religion introduces a neglected field of research with the aim to outline previous and contemporary research, and suggest how the topic of leaving religion should be studied in the future. The handbook consists of three sections covering: 1) Major debates about leaving religion; 2) Case studies and empirical insights; and 3) Theoretical and methodological approaches. Section One deals mainly with the so-called World Religions and it provides the reader with an introduction to key terms, historical developments, major controversies and significant cases. Section Two includes case studies that illustrate various processes of leaving religion from different perspectives, and each chapter provide new empirical insights. Section Three discusses, presents and encourages new approaches to the study of leaving religion by bringing in theoretical and methodological viewpoints from psychology, sociology, geography, history, statistics, narratology and autobiography, and media and communication approaches